Childhood neglect and suicidal behavior: Findings from the National Comorbidity Survey Replication. (May 2020) - Stickley, Andrew; Waldman, Kyle; Ueda, Michiko; Koyanagi, Ai; Sumiyoshi, Tomiki; Narita, Zui; Inoue, Yosuke; DeVylder, Jordan E.; Oh, Hans
Abstract: Background: Although child neglect is common, there has been comparatively little research on it or its specific forms and their effects on mental health in adulthood. Objective: This study aimed to examine the association between exposure to different forms of childhood neglect and lifetime suicidal behavior among a nationally representative sample of adults in the U.S. general population. Methods: Data were analyzed from 5665 adults that were drawn from the National Comorbidity Survey Replication (NCS-R). Information was obtained on 'care', 'supervisory' and 'medical' neglect in childhood and lifetime suicidal behavior (ideation, plan, attempt). Lifetime psychiatric disorders were based on the World Mental Health - Composite International Diagnostic Interview. Logistic regression analysis was used to examine the associations. Results: In fully adjusted models, any neglect was associated with significantly increased odds for all forms of suicidal behavior (suicidal ideation, odds ratio [OR]: 1.80, 95 % confidence interval [CI]: 1.42–2.29; plan, OR: 2.27, 95 % CI: 1.78–2.91; attempt, OR: 2.05, 95 % CI: 1.63–2.59, all p < 0.001). In unadjusted analyses all individual forms of neglect were significantly associated with all forms of suicidal behavior. However, when all forms of neglect were included together in the fully adjusted models, care neglect was no longer significantly associated with any form of suicidal behavior. Conclusion: Different forms of childhood neglect are associated with suicidal behavior in adults independent of common mental disorders. Future studies should focus on childhood neglect subtypes in order to better understand the effects of neglect on adult mental health.